Simulation of Lithuanian Version of DVB–T System - Deksnys, V.; Čitavičius, A. (Elektronika ir Elektrotechnika, 2009)
This paper deals with the SIMULINK model of DVB–T system with parameters settled in Lithuania. Special attention has been given to the design of the tuner phase noise model. The simulation results are presented. The critical values of signal–to–noise ratio in the channel and phase noise level of the tuner determining the critical value of bit error rate were estimated. Ill. 5, bibl. 11 (in English; abstracts in English, Russian and Lithuanian).